Emerging carbon dioxide hotspots in East Asia identified by a top-down inventory - Lei Xia; Rui Liu; Wenxuan Fan; Changxu Ren (Communications Earth & Environment)
Abstract A high-resolution carbon dioxide emission inventory is essential for accurate carbon emission assessment and management. This study used a top-down spatial proxy model to develop a high-resolution (1 km) carbon dioxide emission inventory for East Asia from 2012 to 2021. Combining multiple data sources with geographically weighted regressions can improve the accuracy of the spatial distribution of sectors within carbon dioxide inventories. To demonstrate accuracy, we compared our inventory with existing carbon dioxide inventories, such as the Multi-resolution Emission Inventory for China, which uses a ‘bottom-up’ approach. We outline and discuss the convergence and divergence in the estimation results of the different approaches, finding generally consistent results. Based on the high-resolution carbon dioxide grid, nationally, China accounted for over 80% of East Asia’s carbon dioxide emissions, followed by Japan and South Korea. The results of the hotspot and driver analyses reveal persistent hotspots in Northern and Eastern China, as well as new trends in Northwestern China. The main drivers of emissions growth in hotspots are economic growth and changes in the energy mix. The drivers of emission changes in cold hotspot regions vary depending on regional characteristics. Actionable insights are provided for targeted regional carbon reduction strategies.